Mobility, satisfaction with functional capacity and perceived quality of life (PQOL) in older persons with self-reported visual impairment: The pathway between ability to get around and PQOL - Yeung, Polly; Towers, A.; La Grow, S.; Philipp, M.; Alpass, F.; Stephens, C. (Informa Healthcare, 2015)
Research shows that ability to get around (AGA) is significantly associated with perceived quality of life (PQOL) among older persons with self-reported visual impairment. Much of this impact, however, is through satisfaction with one's functional capacity. Satisfaction with functional capacity is a construct composed of five items: satisfaction with (1) activities of daily living, (2) capacity to work, (3) self, (4) health and (5) sleep. At present, it is not known how AGA interacts individually with these items to influence PQOL. Purpose: The purpose of this study is to investigate the extent to which AGA interacts with each of these five items to affect PQOL. Methods: Structural equation modelling was employed in a secondary-analysis of data from 356 persons (aged 56-72) with self-reported visual impairment to identify the pathways by which AGA affects PQOL. Results: Satisfaction with self and health were the only items found to be both directly related to QOL and to provide a significant pathway between AGA and PQOL.Conclusion: AGA significantly affects PQOL both directly and indirectly through its impact on people's satisfaction with self and health. Lessons may be learnt from this to better focus mobility interventions to enhance PQOL in this population. Implications for Rehabilitation: The findings of this study indicate that ability to get around (AGA) has a significant impact on perceived quality of life (PQOL): the stated goal of many rehabilitation programs for older persons who are visually impaired. The study also found that the primary pathway by which AGA influenced PQOL was indirect through its association with both satisfaction with one's self and health rather than direct. Attempts to enhance PQOL by increasing AGA may be most effective if the focus of intervention was on restoring one's sense of self and health as opposed to focusing on meeting practical needs.